Towards Customer Satisfaction: The Role of Customer Relationship Management, Service Quality, and Customer Perceptions - Bupu, Roswita; Sodikin, Mohamad; Sanchita, Sanchita (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2023)
Orientation and focus on customer satisfaction is an important part of efforts to improve sustainable organizational performance. The Customer Relationship Management (CRM) strategy is part of an effort to find, collect, store information about customers and implement it in all parts of the organization so as to provide a unique experience for customers. However, most of the previous studies have focused on the effect of CRM on companies and few have reviewed CRM in the context of customer perceptions. Drawing based on congruity theory, this study aims to examine the effect of CRM on customer satisfaction through the mediating role of customer perceptions and service quality. Through random sampling, 87 data were obtained from customers who used the services of PT Jasco Logistics Semarang. Data was obtained using a questionnaire with the consent of the respondents. Then analyzed using Partial Least Square (PLS) with the Smart PLS 3.0 program application. The results of this study indicate that Customer Relationship Management (CRM) indirectly has a significant influence on customer satisfaction through service quality and perceived customer perceptions. It was also found that customer perception and service quality directly contribute significantly to customer satisfaction. However, service quality has a greater influence through customer perceptions. These findings provide significant insight for practitioners that in building a CRM strategy it must be able to provide a unique and valuable experience that is felt by customers, so that this will trigger satisfaction.